Concepções de relação ser humano-natureza nos livros de literatura infantil para o ensino fundamental do Programa Nacional Biblioteca da Escola 2008 - Caretti, Luciana da Silva (2011)
The model of society in which we operate does not guarantee and does not claim the right to a dignified life for all, since inequality prevails among the people. We believe that rationality is a greater bearing on the dichotomy between humans and nature is necessary for the construction of new forms of relating. Education emerges as a field of great importance to tackling environmental issues and to incorporate this dimension supports several methodologies, procedures, concepts and frameworks that guide the different practices in environmental education. In a critical perspective, environmental education role to assign collective participation and the educational work consistent with the pursuit of social and environmental transformation of reality. Concerned with the enhancement of life, with the present and future generations, to care for the environment, developing new ways of thinking about reality. These concerns must be present at school and also in materials that circulate in it, such as books, children's literature - rooted these ideals through reading, because we believe that when we read we get in touch with the world beyond, and from this experience, we have generated important tools for the formation of our own world. Aiming to encourage reading, the federal government implemented in 1997 the National Program for School Libraries (PNBE), which annually sends collections of various kinds of books to public schools in Brazil. This work attempts to draw a relationship between the books of children's literature and environmental education through the analysis of the works belonging to the collection for the school's 2008 PNBE addressing environmental issues. Aiming to understand the conceptions of environment present in books, guided by the classification Sauvé suggested in 2005 about the many relationships we have with the environment. The author has mapped current fifteen in environmental education, some of the older tradition and more recent. For the categorization of data, the method of discursive textual analysis. Our corpus consisted of seven books, each book was fragmented and subjected to categorization. To complement this categorization, we created a script in which proposing some parameters that are considered important in an approach to environmental issues. The communication of the senses in the books read was made by metatexts presented in text and systematized in tables. The mainstream was the naturalist and believe that one of the factors that enabled this occurrence were the creation dates of most of the works, between the years 1970 and 1990, by which time the currents prevailed earlier. According to the analysis we conducted, we noticed that most of the books offers many opportunities for work in the field of critical environmental education in the classroom, and good tools for problematizations about environmental issues and important tools in the formation of readers.